2017
DOI: 10.1002/bies.201700076
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic essentiality: Targeting tumor suppressor deficiencies in cancer

Abstract: In this review, we summarize recent work exploring a novel conceptual approach termed "synthetic essentiality" as a means for targeting specific tumor suppressor gene deficiencies in cancer. With the aid of extensive publically available cancer genome and clinical databases, "synthetic essentiality" could be utilized to identify synthetic essential genes, which might be occasionally deleted in some cancers but almost always retained in the context of a specific tumor suppressor deficiency. Synthetic essentiali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Upon the loss of a bona fide tumor suppressor gene through genetic aberrations, a neighboring passenger gene is often homozygously or heterozygously lost as well. These neighboring gene losses were considered futile, but in recent studies it has been demonstrated that the genes located at these loci may play important roles in a variety of key metabolic and regulatory functions, and the subsequent decrease in expression can be exploited as treatment strategy 10,33,34 . Further investigation of collateral lethal hits could lead to the identification of future targets for therapy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon the loss of a bona fide tumor suppressor gene through genetic aberrations, a neighboring passenger gene is often homozygously or heterozygously lost as well. These neighboring gene losses were considered futile, but in recent studies it has been demonstrated that the genes located at these loci may play important roles in a variety of key metabolic and regulatory functions, and the subsequent decrease in expression can be exploited as treatment strategy 10,33,34 . Further investigation of collateral lethal hits could lead to the identification of future targets for therapy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar concept is “collateral lethality,” in which passenger genomic events in tumor cells can create unintended vulnerabilities, particularly in the deletion of redundant essential housekeeping genes . A related concept is “synthetic essentiality,” in which genes that may be deleted in some cancers, are almost always retained in the context of a specific tumor suppressor deficiency, and may represent therapeutic vulnerabilities . Synthetic essential genes may be identified with the aid of available cancer genome and clinical databases, by examining for genes that exhibit mutually exclusive deletion patterns .…”
Section: Synthetic Essentiality: Targeting Genetic Heterogeneity In Pmentioning
confidence: 99%
“…A related concept is “synthetic essentiality,” in which genes that may be deleted in some cancers, are almost always retained in the context of a specific tumor suppressor deficiency, and may represent therapeutic vulnerabilities . Synthetic essential genes may be identified with the aid of available cancer genome and clinical databases, by examining for genes that exhibit mutually exclusive deletion patterns . Zhao et al identified the epigenetic regulator CHD1 as being deleted in some prostate cancers in a mutually exclusive manner with PTEN .…”
Section: Synthetic Essentiality: Targeting Genetic Heterogeneity In Pmentioning
confidence: 99%
“…The rapid realization that there was “addiction” even to non-oncogenic proteins opened up an even larger array of possible targets 24 . The use of large-scale small interfering RNA and short hairpin RNA screens revealed not only gain-of-function mutations that could be therapeutically approached yet also more challenging but, perhaps more interesting, loss-of-function mutations or deletions that are possible synthetic lethality participants 25 , 26 . Some of these synthetic lethality leads fell victim to the common pitfalls that often occur during preclinical cancer target validation, including the well-known off-target effects of small interfering RNA and short hairpin RNA 13 .…”
Section: Empirical Approaches To Discovering Cancer Drug Combination mentioning
confidence: 99%